2014
DOI: 10.1093/ije/dyu056
|View full text |Cite
|
Sign up to set email alerts
|

The effects of media reports of suicides by well-known figures between 1989 and 2010 in Japan

Abstract: This study presents evidence that media reports on celebrity suicides have an immediate impact on the number of suicides in the general population. Our findings also highlight the importance of responsible and cautious media reporting on suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 21 publications
2
31
2
1
Order By: Relevance
“…Consistent with previous literature, articles about suicide in celebrities; 4,12,[16][17][18][19][20][32][33][34][35] by asphyxia other than by car exhaust (i.e., by plastic bag or helium gas, but not hanging or car exhaust) [36][37][38][39][40][41] or by jumping; 5,16 suicide pacts; 21 and that included the method in the headline 21 were each independently associated with post-item increases in suicides. It is particularly noteworthy that articles emphasizing the inevitability of suicide were associated with increased subsequent deaths.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Consistent with previous literature, articles about suicide in celebrities; 4,12,[16][17][18][19][20][32][33][34][35] by asphyxia other than by car exhaust (i.e., by plastic bag or helium gas, but not hanging or car exhaust) [36][37][38][39][40][41] or by jumping; 5,16 suicide pacts; 21 and that included the method in the headline 21 were each independently associated with post-item increases in suicides. It is particularly noteworthy that articles emphasizing the inevitability of suicide were associated with increased subsequent deaths.…”
Section: Discussionsupporting
confidence: 73%
“…However, a previous study has identified that certain overarching narrative arcs of an article may have differing impacts, 5 and the same may be the case for clusters of stories about a specific news event. 4,12,14,16,20,21,32 This study design did not test either phenomenon, both of which are relevant for future recommendations and should be the focus of further research in Canada. Moreover, the fact that sensitivity analyses that compared year of publication as well as print and online articles yielded subtle differences (Appendices 3 and 4) underscores the importance of format as well as other contextual factors, not all of which could be controlled for, and some of which may have influenced the results of this study.…”
Section: Limitationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our calculations suggest that projected changes in suicide rates under future climate change could be as important as other well-studied societal or policy determinants of suicide rates (see Figure 5 left panel). In absolute value, the effect of climate change on the suicide rate in the US and Mexico by 2050 is roughly two to four times the estimated effect of a 1% increase in the unemployment rate in the EU, 5 half as large as the immediate effect of a celebrity suicide in Japan, 48 and roughly one-third as large in absolute magnitude (with opposite sign) as the estimated effect of gun restriction laws in the US 7 or the effect of national suicide prevention programs in OECD countries. 6 The large magnitude of our results add further impetus to better understand why temperature affects suicide and to implement policies to mitigate future temperature rise.…”
Section: Discussionmentioning
confidence: 99%
“…Clustering of suicide cases has been described in the literature [23], including a type of geographical but not temporal clustering. Postulated psychological/social mechanisms comprise imitation, modeling effect, and information sharing about the suicide of a significant other (similar to the case of celebrity suicides in industrialized societies [24]). In very isolated and small sized indigenous groups, where people are close to each other, imitation (e.g.…”
Section: Discussionmentioning
confidence: 99%